A simple method for the determination of bioethanol from lignocellulosic materials using gas chromatography-flame ionisation detector (GC-FID) - Mohamed Ghazali, Mona Fatin Syazwanee; Mustaf, Muskhazli; Mohd Zainudin, Nur Ain Izzati; Abd Aziz, Nor Azwady (EBSCO Industries, 2022)
Aims: The utilisation of lignocellulosic biomass for bioethanol production reduces the dependency on fossil fuels as a source of energy and emission of greenhouse gas (GHG). However, studies in this emerging field are hampered by the cost of ethanol quantification methods. Due to the volatile nature of ethanol, the method for the quantification of bioethanol production should be reproducible and rapid to avoid any evaporation loss to the surroundings. Therefore, this study aimed to develop a simple, rapid and precise bioethanol quantification method using a gas chromatography- flame ionisation detector (GC-FID) without having to go through distillation process for ethanol purification. Methodology and results: The bioethanol was produced via consolidated bioprocessing (CBP) using Trichoderma asperellum B1581 and paddy straw. The peak corresponding to ethanol was obtained at 2.347 min with a peak area of 189.66, equating to 0.159% (v/v) or 1.25 g/L ethanol. A comparison between the quantity of ethanol detected by GC-FID and spectrophotometric analysis (340 nm) showed no significant difference (p>0.05) in the amount of ethanol detected by GC analysis, thus validating the accuracy of the GC method. Conclusion, significance and impact of study: This work presents a simple, precise and reliable method to determine the amount of bioethanol in the sample using a GC-FID. Currently, there are many GC-FID methods available for the determination of ethanol/alcohol in a human blood samples or in beverages but not in bioethanol samples. Thus, this method was developed to facilitate the determination of bioethanol in the samples produced from lignocellulosic materials.